2005
DOI: 10.1590/s1415-47572005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for test-day milk yield in Holstein cows using a random regression model

Abstract: Test-day milk yield records of 11,023 first-parity Holstein cows were used to estimate genetic parameters for milk yield during different lactation periods. (Co)variance components were estimated using two random regression models, RRM1 and RRM2, and the restricted maximum likelihood method, compared by the likelihood ratio test. Additive genetic variances determined by RRM1 and additive genetic and permanent environmental variances estimated by RRM2 were described, using the Wilmink function. Residual varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
34
4
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 21 publications
30
34
4
4
Order By: Relevance
“…B-spline and Wilmink showed similar estimates. Several studies in Holstein cattle using RRM reported similar trend for TD heritability estimates as obtained in this study, Olori et al (1999) and Kettunen et al (2000), and in Brazil by Cobuci et al (2005), Araújo et al (2006), Melo et al (2007) and Dorneles et al (2009).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…B-spline and Wilmink showed similar estimates. Several studies in Holstein cattle using RRM reported similar trend for TD heritability estimates as obtained in this study, Olori et al (1999) and Kettunen et al (2000), and in Brazil by Cobuci et al (2005), Araújo et al (2006), Melo et al (2007) and Dorneles et al (2009).…”
Section: Resultssupporting
confidence: 87%
“…The highest permanent environmental variances (not shown) estimated with the RRM were observed at the beginning and at the end of lactation. The same trend for Holstein cattle has been reported by Melo et al (2003), Cobuci et al (2005) and Costa et al (2008) and indicates that environmental factors exerted a marked influence during these periods.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Esse aumento nas estimativas de herdabilidade está parcialmente associado à redução da variância de ambiente permanente que promoveu redução na variância total e, conseqüente, aumento da contribuição proporcional da variância genética aditiva. Essa tendência crescente assemelha-se às relatadas por Melo (2003) e Cobuci et al (2005), para a raça Holandesa, usando a função de Wilmink para modelar as variâncias genéticas e de ambiente permanente.…”
Section: Introductionunclassified
“…Da mesma maneira, como o arquivo CT possuía menor número de informações, a superfície apresentou oscilações mais visíveis que para as demais estruturas. De maneira geral, as correlações fenotípicas foram maiores entre os controles adjacentes e apresentaram menores magnitudes que as correlações genéticas, sendo as magnitudes, próximas às encontradas por COBUCI et al (2005), FERREIRA et al (2003 e MELO et al (2005). As correlações de ambiente permanente para os diferentes arquivos de dados analisados apresentaram superfícies e tendências muito próximas, mantendo o mesmo comportamento das correlações anteriores.…”
Section: Resultsunclassified